EFFECT OF THE DEVELOPMENT OF COMMUNICATION INFORMATION TECHNOLOGY ON LOCAL CULTURAL EXISTENCE - Robby Darwis Nasution (Jurnal Penelitian Komunikasi dan Opini Publik, 2017)
The development of technology and information brings the impact of the entry of Western culture and create changes in patterns of behavior of people who tend to westernization. Globalization which is followed by the rapid development of information and communication technology is also a major trigger of Western cultural acculturation to Indigenous cultures. Cyberspace has entered the era of Second Media Age where the number of growth of internet users in the world is increasing sharply as well as in Indonesia. In Indonesia the number of smartphone users reached 41.3 million users which means the number of internet users is also high. The effect of the development of information and communication access is the occurrence of cultural globalization which has eliminated boundaries and legitimacy through an ideology of progress. The loss of legitimacy of this boundary will ultimately be a major threat to the local culture against the onslaught of Western culture, so the most likely option is to become a Global Homogeneity or even grow local cultural Maturity. Resistance to values that are not in accordance with our local culture will be directly rejected or filtered by our local culture. The key to the success of this filtering is how strongly our local culture, norms or customs are and how strong they are as our ideologies in everyday life. If our culture, norms or customs do not stick strongly as the ideologies we hold on a daily basis it is very likely the loss of our local culture and transform into Global Homogeneity, and if our culture is firmly established as an ideology we hold on a daily basis then westernisation will not Can damage our local culture so that what happens is our local cultural maturity. Keywords: globalization, technology development, local culture, westernization  Perkembangan teknologi dan informasi membawa dampak masuknya budaya Barat dan menciptaka perubahan pola perilaku masyarakat yang condong ke westernisasi. Globalisasi yang diikuti dengan perkembangan teknologi informasi dan komunikasi yang semakin cepat juga menjadi pemicu utama akulturasi budaya Barat terhadap budaya Pribumi. Cyberspace telah memasuki masa Second Media Age dimana jumlah pertumbuhan pengguna internet di dunia semakin meningkat tajam begitu juga di Indonesia. Di Indonesia jumlah pengguna smartphone mencapai 41,3 juta pengguna yang ini berarti jumlah pengguna internet juga tinggi. Efek yang ditimbulkan dari perkembangan akses informasi dan komunikasi adalah terjadinya globalisasi budaya dimana telah menghilangkan batas serta legitimasi melalui sebuah ideologi kemajuan. Hilangnya legitimasi batas ini pada akhirnya akan menjadi ancaman utama bagi budaya lokal terhadap gempuran budaya Barat, sehingga pilihan yang mungin terjadi adalah menjadi Homogenitas Global atau malah tumbuh Kedewasaan budaya lokal. Resistensi terhadap nilai-nilai yang tidak sesuai dengan budaya lokal kita maka secara langsung akan ditolak atau dilakukan filtering oleh budaya lokal kita. Kunci utama dari keberhasilan dari filterisasi ini adalah seberapa kuat budaya, norma ataupun adat lokal yang kita miliki dan seberapa kuat budaya tersebut menancap sebagai ideologi kita di kehidupan sehari-hari. Jika budaya, norma atau adat kita tidak menancap kuat sebagai ideologi yang kita pegang teguh setiap hari maka sangat mungkin hilangnya budaya lokal kita dan berubah menjadi Homogenitas Global, dan begitupun jika budaya kita menancap kuat sebagai ideologi yang kita pegang teguh setiap hari maka westernisasi tidak akan bisa merusak budaya lokal kita sehingga yang terjadi adalah kedewasaan budaya lokal kita. Kata Kunci : globalisasi, perkembangan teknologi, budaya lokal, westernisasi